Resources Distribution and Gender Development Among The Local Level in Lalitpur and Jhapa Districts - Parajuli, Pradip; Sijapati, Dipendra Bikram (Patan Prospective Journal, 2022)
This article focused on resource distribution and Gender development at the local level.There are two objectives such as to find out the local resources distribution in the different local governments of Jhapa and Lalitpur District and to examine the involving the decision-making of council meetings and policy making process and practices in the gender development sector. Nepal highly prioritized gender development as well as at well budgetary policy formulation for adopting perception and concept of development. This paper is based on descriptive and analytical types of research design. It has used both quantitative and qualitative methods of data collection and deductive and inductive approaches to the analysis of these collected data. Information is gathered and assessed on the process of resource distribution and Gender development at the local level. The elected local government bodies have formulated the income generated and skill development plans and programs around 5 times a year. Furthermore, the highest percent of respondents of all local areas of both districts, have a practice of allocating the gender-friendly budget in local government and budgets supporting women's capacity building and empowerment and 1-5 lakhs budgets are allocated for the above-mentioned purpose. But those allocated amounts are adequate only for one-third part of the women's development sectors. The local government have formulated the evaluation and monitoring committee for those types of program activities, male and female local government elected personnel are involved in monitoring and evaluating activities of such programs activities.